THE EFFECT OF PICTORIAL TEACHING TECHNIQUE AND KWL TEACHING TECHNIQUE ON PUPILS READING COMPREHENSION - Masriani Mery Rosmida Silalahi (Sean Institute, 2021)
This study deals with the effect of Pictorial teaching technique and KWL teaching technique on pupils reading comprehension. It is intended to prove that the hypothesis is accepted. The research is quantitative research. The population was pupils of grade VII of SMP Budi Utomo and samples were taken from 2 classes of Grade VII by cluster random sampling. The groups were taught by Pictorial teaching technique and KWL teaching technique. Multiple choice and short answer were used as the instrument for collecting data. The data was analyzed by t-test formula. It was found that t-observed was 2.876 and it was higher than t-table, 2.000, at the level of significance of 0.05. It was proved that using Pictorial teaching technique affected the students’ ability in comprehending expository text.